Rekonstruksi Pemikiran Pragmatisme John Dewey dan Relevansinya dalam Pendidikan Islam Kontemporer - Muhammad Ihsan Siregar; Maragustam Maragustam; Ifone Shiflana Habiba (Akhlak : Jurnal Pendidikan Agama Islam dan Filsafat, 2026)
In the context of educational development characterized by technological advancement, dynamic social change, and increasing demands for critical thinking and problem-solving skills, there is a need for learning approaches that are not merely theoretical but also contextual, practical, and experience-based. This study aims to analyze John Dewey’s concept of pragmatism and its relevance to contemporary Islamic education. The research employs a qualitative approach using a library research method. The primary data source is John Dewey’s seminal work Democracy and Education (1916), supported by various scholarly literature on Islamic education. Data were collected through documentation techniques and analyzed using content analysis. The findings reveal that John Dewey’s pragmatism emphasizes experience as the primary foundation of learning through the concepts of instrumentalism, the theory of experience, inquiry logic, progressive education, and democratic and social education, all of which position education as an active, contextual, and problem-solving-oriented process. In the context of Islamic education, these concepts are relevant for strengthening experiential learning, implementing learning by doing, and developing students’ critical and participatory thinking skills. Nevertheless, a fundamental epistemological difference exists, as pragmatism is grounded in empirical experience, whereas Islamic education is based on divine revelation. Therefore, the application of Dewey’s pragmatism in Islamic education should be carried out selectively and critically, treating it primarily as a methodological approach. Thus, John Dewey’s pragmatism can contribute to the development of Islamic education that is more contextual, practical, and responsive to contemporary challenges.